2005
DOI: 10.1007/s10535-005-0272-6
|View full text |Cite
|
Sign up to set email alerts
|

Water-use efficiency and carbon isotope discrimination of Acacia ampliceps and Eucalyptus camaldulensis at different soil moisture regimes under semi-arid conditions

Abstract: Acacia ampliceps Maslin and Eucalyptus camaldulensis Dehnh. were grown for one year in lysimeters at three soil moisture regimes: 100 % (well-watered), 75 % (medium-watered) and 50 % (low-watered) of total plant available water. Biomass yield of both species increased with increase in soil moisture. Water-use efficiency (WUE) of E. camaldulensis decreased and that of A. ampliceps increased markedly with decrease in available soil moisture. A. ampliceps showed 4 -5 times more biomass yield than E. camaldulensis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…The decrease in WUE of B. faberi var. microphylla seedlings under water stress, contradicts the finding with some species (Hubick et al 1986;Liu et al 2005;Maggio et al 2005), and agrees with reports on crops (Zhao et al 2004;Clavel et al 2005) and on Acacia ampliceps (Akhter et al 2005). Engelbrecht et al (2005) suggested that decreased WUE in water-stressed seedlings might be related to their root systems which are not well-established to acquire water from lower soil layers.…”
Section: Discussionsupporting
confidence: 74%
“…The decrease in WUE of B. faberi var. microphylla seedlings under water stress, contradicts the finding with some species (Hubick et al 1986;Liu et al 2005;Maggio et al 2005), and agrees with reports on crops (Zhao et al 2004;Clavel et al 2005) and on Acacia ampliceps (Akhter et al 2005). Engelbrecht et al (2005) suggested that decreased WUE in water-stressed seedlings might be related to their root systems which are not well-established to acquire water from lower soil layers.…”
Section: Discussionsupporting
confidence: 74%
“…Although many studies have found that the WUE of woody seedlings increased with increasing water stress (Kramer and Boyer, 1995;Yin et al, 2004;Akhter et al, 2005;Rodiyati et al, 2005;Bacelar et al, 2007;Gonzáles et al, 2008), it is still unclear about how plant WUE changes with water stress intensity. Our results along the water stress gradient with five levels provided good opportunity to explore it.…”
Section: The Morphological and Anatomical Modifications In Response Tmentioning
confidence: 99%
“…It has been found that the WUE is lower in water-stressed plants than in well-watered plants (Rodiyati et al, 2005;Bacelar et al, 2007) and believed that stomatal closure leads to a lower level of water loss per carbon assimilation, thereby improving the water-use efficiency (WUE) in water-stressed plants (Kramer and Boyer, 1995;Akhter et al, 2005;Gonzáles et al, 2008). However, the results keep to be controversial, because improving WUE may conflict with the high growth rate for many species (Hubick et al, 1986;Akhter et al, 2005;Wu et al, 2008a). The controversy focus is how plant WUE changes with water stress intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Eucalyptus are known to have high water uptake which is primarily a strategy enabling them to grow even under harsh environmental conditions (Akhter et al, 2005). This high water uptake capacity enables them to outcompete other plants occurring in their vicinity.…”
Section: Eucalypt and Maize Competitionmentioning
confidence: 99%